2012
DOI: 10.2527/jas.2011-4797
|View full text |Cite
|
Sign up to set email alerts
|

Identification and association analysis of several hundred single nucleotide polymorphisms within candidate genes for back fat thickness in Italian Large White pigs using a selective genotyping approach1

Abstract: Combining different approaches (resequencing of portions of 54 obesity candidate genes, literature mining for pig markers associated with fat deposition or related traits in 77 genes, and in silico mining of porcine expressed sequence tags and other sequences available in databases), we identified and analyzed 736 SNP within candidate genes to identify markers associated with back fat thickness (BFT) in Italian Large White sows. Animals were chosen using a selective genotyping approach according to their EBV f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 87 publications
2
63
0
1
Order By: Relevance
“…How AS160 and Tbc1d1 control body weight, energy expenditure, and fatty acid oxidation is currently not known. But Tbc1d1 mutations and single nucleotide polymorphisms are associated with body weight and body composition changes in animals (4,12,37,38) and with obesity in humans (16,20,23,31).…”
Section: /Tbc1d1mentioning
confidence: 99%
“…How AS160 and Tbc1d1 control body weight, energy expenditure, and fatty acid oxidation is currently not known. But Tbc1d1 mutations and single nucleotide polymorphisms are associated with body weight and body composition changes in animals (4,12,37,38) and with obesity in humans (16,20,23,31).…”
Section: /Tbc1d1mentioning
confidence: 99%
“…Studies of CasasCarrillo et al (1997) and Assis de Faria et al (2009) based on microsatellite analyses (including the IGF1 short tandem repeat marker) indicated that this chromosome region harbours QTL for growth and carcass traits. However, previous genome wide association studies we conducted on Italian Large White pigs by using single nucleotide polymorphisms in a few hundred candidate genes and the Illumina PorcineSNP60 BeadChip tool did not show any marker significantly associated with BFT in the region of SSC5 located around IGF1 (Fontanesi et al, 2012b(Fontanesi et al, , 2012c. These results would indicate that no important segregating SSC5QTL, at least for BFT, might be present in this breed.…”
Section: Association Analyses In Italian Large White and Italian Duromentioning
confidence: 58%
“…The first group of the selective genotyping approach was constituted by 560 Italian Large White gilts with no common parents, selected among ~12,000 performance tested pigs of this breed in the period 1995-2007 (Fontanesi et al, 2012b Fontanesi et al, 2008Fontanesi et al, , 2010 (Fontanesi et al, 2010).…”
Section: Animalsmentioning
confidence: 99%
“…On the other hand, an interaction among and within loci may also be shown in the ranking of chromosomes. Complex genetic determination of meatness has been reported by a number of authors (Kamiński et al, 2009;Srikanchai et al, 2010;Weisz et al, 2011;Fontanesi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%